2007
DOI: 10.1002/path.2169
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis is a marker for hepatocellular carcinomas displaying β‐catenin mutations

Abstract: The Wnt/beta-catenin signalling pathway is activated in many human hepatocellular carcinomas (HCC). Identification of beta-catenin mutation relies mostly on sequence analysis and/or immunohistochemistry. beta-catenin mutation may also be detected by analysing the expression of its target genes. The GLUL gene encoding glutamine synthetase (GS), for example, appears to be a pertinent marker. The aim of this study was to correlate GS immunostaining and beta-catenin mutations with clinicopathological features in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 30 publications
(39 reference statements)
10
133
1
1
Order By: Relevance
“…51 Most importantly, GS is a target gene of ␤-catenin so that its overexpression is associated with mutations of ␤-catenin or with activation of this pathway. [52][53][54] Up-regulation of GS messenger RNA, protein, and activity were shown by Christa et al 52 in human HCC, while Osada et al 55 reported the stepwise increase in GS immunoreactivity from precancerous lesions to early HCC to progressed HCC. The monoclonal antibody from Chemicon International (clone MB302) at a dilution of 1/500 to 1/1000 and amplified with a new short polymer system yields reliable results.…”
Section: Emerging Tumor Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Most importantly, GS is a target gene of ␤-catenin so that its overexpression is associated with mutations of ␤-catenin or with activation of this pathway. [52][53][54] Up-regulation of GS messenger RNA, protein, and activity were shown by Christa et al 52 in human HCC, while Osada et al 55 reported the stepwise increase in GS immunoreactivity from precancerous lesions to early HCC to progressed HCC. The monoclonal antibody from Chemicon International (clone MB302) at a dilution of 1/500 to 1/1000 and amplified with a new short polymer system yields reliable results.…”
Section: Emerging Tumor Markersmentioning
confidence: 99%
“…29 New immunohistochemical and molecular markers are still under investigation and are likely to prove useful. 46,54,56 Role of Liver Biopsy. Regarding the application of biopsy for small nodules, the American Association for the Study of Liver Diseases recommends that biopsy should be performed for nodules less than 2 cm if their radiologic findings are not characteristic of HCC, whereas biopsy is not needed for lesions showing characteristic radiologic findings.…”
Section: Commentmentioning
confidence: 99%
“…The liver-type glutaminase 2, which catalyzes the conversion of glutamine to glutamate is almost absent or significantly decreased in human HCC [91]. Consistently, the expression of glutamine synthetase, which catalyzes the opposite reaction, is increased in HCC patients with β-catenin mutations [92][93][94]. Glutamine synthetase is a target gene of β-catenin and overexpression of glutamine synthetase is highly correlated with β-catenin mutations [92], which in turn is related to early-stage HCC [95].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 81%
“…Consistently, the expression of glutamine synthetase, which catalyzes the opposite reaction, is increased in HCC patients with β-catenin mutations [92][93][94]. Glutamine synthetase is a target gene of β-catenin and overexpression of glutamine synthetase is highly correlated with β-catenin mutations [92], which in turn is related to early-stage HCC [95]. Moreover, glutamine synthetase expression is correlated with HCC progression [93,96].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 85%
See 1 more Smart Citation